2015
DOI: 10.1111/jog.12819
|View full text |Cite
|
Sign up to set email alerts
|

Predictors affecting breast self‐examination practice among undergraduate female students in Klang Valley, Malaysia

Abstract: Aim: Breast cancer is the most common cancer among women worldwide, including Malaysia. In developing countries, predictors affecting breast self-examination (BSE) practice are different. This cross-sectional study was conducted to determine the prevalence of BSE practice and the predictors affecting BSE practice among undergraduate female students in Klang Valley, Malaysia. Material and Methods: A cross-sectional study was conducted among 820 female undergraduate students to assess the BSE performance and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
(27 reference statements)
0
8
1
Order By: Relevance
“…Our study showed that only 14.7% of the college students performed BSE, which needs enhancement and deserves social attention. This result is slightly less than similar studies conducted in Malaysia (19.6%), 24 Ethiopia (21.4%), 19 and Iran (24.6%) 20 targeting female students. The different results may be due to the methodological and regional differences.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Our study showed that only 14.7% of the college students performed BSE, which needs enhancement and deserves social attention. This result is slightly less than similar studies conducted in Malaysia (19.6%), 24 Ethiopia (21.4%), 19 and Iran (24.6%) 20 targeting female students. The different results may be due to the methodological and regional differences.…”
Section: Discussioncontrasting
confidence: 68%
“…On the contrary, fear, anxiety, and embarrassment were described as barriers of BSE practice. 18,24,39 Furthermore, attitudes towards breast cancer play the intermediary role between knowledge and BSE performance. This indicates that the positive psychological factors are beneficial for the students to carry out BSE actively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Third National Health Morbidity Survey [ 6 ], the prevalence rate for breast examination in Malaysia was 70.35 %, where the highest was for breast self-examination (57.14 %), followed by clinical breast examination (51.77 %) and mammography (7.57 %) [ 6 ]. Based on the results of another studies, low percentages of clinical breast examination (23.3 %), breast self-examination (19.6 %), and intention to perform breast self-examination (18.5 %) were observed among Malaysian women [ 7 – 9 ]. Such results clearly show the need for awareness campaigns that raise the knowledge of young women about breast cancer and the need for the involvement of social media in promoting public breast health [ 6 – 9 ].…”
Section: Introductionmentioning
confidence: 99%